1993
DOI: 10.1083/jcb.122.2.461
|View full text |Cite
|
Sign up to set email alerts
|

A cell cycle and mutational analysis of anchorage-independent growth: cell adhesion and TGF-beta 1 control G1/S transit specifically

Abstract: Abstract. We have examined cell cycle control of anchorage-independent growth in nontransformed fibroblasts. In previous studies using Go-synchronized NRK and NIH-3T3 cells, we showed that anchorageindependent growth is regulated by an attachmentdependent transition at G1/S that resembles the START control point in the cell cycle of Saccharomyces cerevisiae. In the studies reported here, we have synchronized NRK and NIH-3T3 fibroblasts immediately after this attachment-dependent transition to determine if othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
28
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(29 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Its presence in both smooth muscle and nonmuscle cells indicates that it may have a cytoskeletal function. Considering calponin's inhibitory activity on actin-myosin interactions, h2-calponin may also play an inhibitory role in regulating the functions of the actin cytoskeleton, such as coordinating changes in cell shape and intracellular molecular trafficking, both of which are critical events in cytokinesis (15). Therefore, h2-calponin may act as a balancing mechanism to maintain the physiological levels of actin filament activity in both smooth muscle and nonmuscle cells.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Its presence in both smooth muscle and nonmuscle cells indicates that it may have a cytoskeletal function. Considering calponin's inhibitory activity on actin-myosin interactions, h2-calponin may also play an inhibitory role in regulating the functions of the actin cytoskeleton, such as coordinating changes in cell shape and intracellular molecular trafficking, both of which are critical events in cytokinesis (15). Therefore, h2-calponin may act as a balancing mechanism to maintain the physiological levels of actin filament activity in both smooth muscle and nonmuscle cells.…”
Section: Discussionmentioning
confidence: 99%
“…The contraction of the contractile ring is most likely generated by the interaction between actin and myosin (2,6,22,27). The actin cytoskeleton has been demonstrated to participate in anchorage-dependent cell division (15), and actin-myosin interactions have been shown to power cell proliferation by driving cytoplasmic streaming. In vitro experiments have shown that calponin inhibits the relative movements of actin and myosin (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Established human and rodent fibroblasts undergo cell cycle arrest in the G 1 phase of the cell cycle when cultured in suspension (19,36,41). Beyond a defined time point in G 1 , cells are no longer dependent on adhesion to complete the cell cycle (6,21). Cell adhesion and spreading involves interaction of integrins with the extracellular matrix and the actin-based cytoskeleton.…”
mentioning
confidence: 99%